Evaluation the Influences of housing quality in rural settlements vitality Khavmyrabad district, Mariwan township - Behrooz Mohammadi yeganeh; Mehdi cheraghi; fovad samadi (تحقیقات کاربردی علوم جغرافیایی)
Research goall is survey in the situation of quality of housing and rural vitality and survey of relationship of housing quality and vitality of rural settlements. The population of research is Khawmirabad county (Kurdestan Province, Mariwan Township) with 2737 households. Research method is analytical –description based on questionnaire and it is applicable research . In order to gathering the data we used documentary and field method and interviews and questionnaire based on Likert scale(five – range opinion)has been used. In order to sampling we used random sampling and by using of Cochran formula that sample size is equal to 290 households. In order to analysis of data’s from questionnaire, we used both of Descriptive (mean and deviation) and Inferential(One sample T, Linear regression, Chi- square) Statistics. The results of this study indicate a low level of economic dimensions (2.34) and political (2.97), vitality and quality of housing than the average (2.74). This difference is statistically significant at the alpha level 0.01 numerical difference utility as evaluation and assessment is negative. The results also show that the greatest impact of the quality of housing is on the social dimension with a beta coefficient of 0/570 and the lowest on the economic dimension with 0/077 beta coefficient.